Available Light : Anthropological Reflections on Philosophical Topics - Geertz, Clifford (Book collections on Project MUSE., 2000)
Clifford Geertz, one of the most influential thinkers of our time, here discusses some of the most urgent issues facing intellectuals today. In this collection of personal and revealing essays, he explores the nature of his anthropological work in relation to a broader public, serving as the foremost spokesperson of his generation of scholars, those who came of age after World War II. His reflections are written in a style that both entertains and disconcerts, as they engage us in topics ranging from moral relativism to the relationship between cultural and psychological differences, from the.